Blekitna zatoka - Roberts, Nora. (Warszawa : Swiat Ksiazki, 2004)
Polish translation of "Chesapeake Blue". The story of Seth Quinn who was abused as a child. He returns home from Europe a grown man and as a fine artist to face the family and its problems.
Keywords: Adult child abuse victims -- Fiction; Poor families -- Fiction; Young men -- Fiction; Adoptees -- Fiction; Chesapeake Bay Region (Md. and Va.) -- Fiction; Eastern Shore (Md. and Va.) -- Fiction; Maryland -- Fiction; Psychological fiction; Love stories